2011
DOI: 10.1016/j.ajpath.2011.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Mediates Aldosterone-Induced Podocyte Damage

Abstract: Aldosterone (Aldo) causes podocyte damage by an unknown mechanism. We examined the role of mitochondrial dysfunction (MtD) in Aldo-treated podocytes in vitro and in vivo. Exposure of podocytes to Aldo reduced nephrin expression dose dependently, accompanied by increased production of reactive oxygen species (ROS). The ROS generation and podocyte damage were abolished by the mitochondrial (mt) respiratory chain complex I inhibitor rotenone. Pronounced MtD, including reduced mt membrane potential, ATP levels, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 45 publications
4
81
1
Order By: Relevance
“…We described that mitochondrial dysfunction is an early event in aldosterone-induced podocyte injury. In an aldosterone-infused mouse model, before fusion of podocyte processes and proteinuria, the mitochondrial membrane potential, copy number of mtDNA, and ATP production start to decease with the increase in ROS production (130,160). In addition, mitochondrial dynamics and quality control processes are involved in podocyte injury.…”
Section: Acquired Mitochondrial Dysfunction In Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…We described that mitochondrial dysfunction is an early event in aldosterone-induced podocyte injury. In an aldosterone-infused mouse model, before fusion of podocyte processes and proteinuria, the mitochondrial membrane potential, copy number of mtDNA, and ATP production start to decease with the increase in ROS production (130,160). In addition, mitochondrial dynamics and quality control processes are involved in podocyte injury.…”
Section: Acquired Mitochondrial Dysfunction In Kidney Diseasementioning
confidence: 99%
“…For example, they were able to reduce proteinuria and fibrotic responses and prevent podocyte as well as vascular injury, in both animal and clinical trials (87,121). Rosiglitazone, one of the TZDs, can effectively inhibit podocyte injury and MC proliferation through reduced ROS production and recovery of mitochondrial electron transport function in vivo and in vitro (65,154,160). TZDs also decrease TGF-␤ production in glomeruli, thus attenuating renal interstitial fibrosis (74).…”
Section: Treatment Of Mitochondrial Dysfunction-induced Kidney Injurymentioning
confidence: 99%
“…Other new therapeutic approaches are also being explored. For example, PPARα protects podocytes from aldosterone-induced mitochondrial dysfunction (32). Glycogen synthetase kinase (GSK) 3β integrates signals that regulate mitochondrial pore transition, and a thiazolidinedione compound that inhibits GSK2β was shown to alleviate doxorubicin-induced podocyte injury in vitro and in vivo (33).…”
Section: Mitochondria and Podocyte Functionmentioning
confidence: 99%
“…Shibata et al [13] observed podocyte injury following increased NADPH oxidase activity in the kidney of aldosterone-infused rats. Another study found that mitochondria dysfunction was associated with higher levels of ROS production and was involved in aldosterone-induced podocyte injury [14,15] . ROS are scavenged by a sophisticated antioxidant defense system that includes enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSHPx).…”
Section: Introductionmentioning
confidence: 99%